2004
DOI: 10.1021/ic0400484
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Jahn−Teller Distortions in Tetrathiolato Iron(II) Complexes

Abstract: Crystallographic studies of [Fe(SR)(4)](2-) (R is an alkyl or aryl residue) have shown that the Fe(II)S(4) cores of these complexes have (pseudo) D2d symmetry. Here we analyze the possibility that these structures result from a Jahn-Teller (JT) distortion that arises from the e(3z(2) - r(2), x(2) - y(2)) orbital ground state of Fe(II) in T(d)symmetry. Special attention is paid to the influence of the second-nearest neighbors of Fe, which lowers the symmetry and reduces the full JT effect to a smaller, pseudo J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The S = 2 state is again the most stable one for the tetrahedron, with the optimized structure slightly deviating from the perfect tetrahedron (S(T d ) = 0.09, bond angles of 106 and 1118) due to a Jahn-Teller effect, as discussed recently by Vrajmasu et al [14] The relative energy of the square geometry for this spin state is now much higher compared to that of the methyl derivative (Figure 1). At the same time, the S = 1 and S = 0 states are strongly destabilized relative to the high spin situation, and only a triplet tetrahedral structure is expected for those compounds.…”
supporting
confidence: 69%
“…The S = 2 state is again the most stable one for the tetrahedron, with the optimized structure slightly deviating from the perfect tetrahedron (S(T d ) = 0.09, bond angles of 106 and 1118) due to a Jahn-Teller effect, as discussed recently by Vrajmasu et al [14] The relative energy of the square geometry for this spin state is now much higher compared to that of the methyl derivative (Figure 1). At the same time, the S = 1 and S = 0 states are strongly destabilized relative to the high spin situation, and only a triplet tetrahedral structure is expected for those compounds.…”
supporting
confidence: 69%
“…between the last two optimization steps. Each optimization started from the same initial wave function and geometry, which eliminated potential conformational differences between optimized structures, which can affect the electronic structure 48, 49…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore it was found that some iron (III) complexes provide a useful structural and electronic model for the similarly coordinated iron (III) sites found in the heme iron enzymes [9]. The tetrahalogenoferrates (III) have been utilized in bioinorganic chemistry as reagents for synthesizing some model compounds, such as [Fe 2 S 2 Cl 4 ] 2- [10,11]. The investiga-tion of the structures and properties of these compounds and their similarities are interested.…”
Section: Introductionmentioning
confidence: 99%